2019
DOI: 10.1186/s12936-019-2874-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex serology demonstrate cumulative prevalence and spatial distribution of malaria in Ethiopia

Abstract: Background Measures of malaria burden using microscopy and rapid diagnostic tests (RDTs) in cross-sectional household surveys may incompletely describe the burden of malaria in low-transmission settings. This study describes the pattern of malaria transmission in Ethiopia using serological antibody estimates derived from a nationwide household survey completed in 2015. Methods Dried blood spot (DBS) samples were collected during the Ethiopian Malaria Indicator Survey in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 32 publications
3
36
2
Order By: Relevance
“…More than 60% of the nPCR positive cases were identified from Benishangul-Gumuz Region, which is one of the higher malaria transmission region in Ethiopia [5]. The region showed a similar high prevalence of malaria by microscopy and RDTs in this study and in a separate serology study of the same samples [21].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…More than 60% of the nPCR positive cases were identified from Benishangul-Gumuz Region, which is one of the higher malaria transmission region in Ethiopia [5]. The region showed a similar high prevalence of malaria by microscopy and RDTs in this study and in a separate serology study of the same samples [21].…”
Section: Discussionsupporting
confidence: 64%
“…From the EMIS-2015 results, rapid diagnostic test (RDT) prevalence ranged from 10.4% in Benishangul-Gumuz, 1.9% in Tigray, to 1.1% in Amhara. A separate study [21] also found this geographical area to represent a range of malaria transmission from very low to moderate based on seroprevalence. Participants tested by malaria microscopy and RDT that provided DBS samples were selected from the EMIS 2015 samples repository at the Ethiopian Public Health Institute (EPHI) in Addis Ababa, Ethiopia.…”
Section: Study Areamentioning
confidence: 87%
See 1 more Smart Citation
“…Despite the lack of a clearly defined relationship between antigen-matched targets from opposing expression systems, we remain confident that microarrays utilising IVTT or purified recombinant proteins are able to produce compelling and biologically relevant data. Indeed, our data show age-dependent trends in antibody responses (typical of highly endemic populations [1][2][3]) irrespective of expression system (Supplementary figure 2), lending weight to the applicability of either methodology in serological assays [33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Ama1 -Ivtt_1mentioning
confidence: 55%
“…Proportion of seropositive for P. falciparum by region ranged from 11.0% in Somali to 65.0% (95% CI: 58.0-71.4) in Gambela Region (31). Given the lower prevalence of malaria in the anemia hotspot areas (eastern Ethiopia), it is less likely that malaria is the cause for the geospatial inequality of anemia in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%